Are we any closer to identifying a causal relationship between cannabis and psychosis?. (April 2021) - Hamilton, Ian; Sumnall, Harry
Highlights: The increasing availability of high potency cannabis increases the risk of developing cannabis psychosis, as a dose response relationship has been established as a risk factor. Defining and standardizing terms and measurement of cannabis products and use could usefully transform research and practice for cannabis psychosis. Evidence based interventions for patients with cannabis psychosis are limited and those that show promise are symptom-specific rather than treating all symptoms. Liberalisation of cannabis policy in some countries may support studies designed to better understand the impact of cannabis on mental health. Abstract : This review provides the reader with an update on developments in research relating to cannabis psychosis. For over four decades researchers and clinicians have focused on the relationship between exposure to cannabis and the emergence of psychotic symptoms. This has proved to be a complicated topic to investigate but research has provided some valuable insights as to the nature of this relationship while also identifying the limits of our understanding. There are significant gaps in understanding of almost every aspect of the journey that people who have cannabis psychosis experience. Not only are treatment options limited, but we still have little evidence to help reliably predict who is at risk of developing cannabis psychosis. This would provide an opportunity to intervene early to reduce the number of people who experience this type of problem, although it is unrealistic to think it would be eliminated completely.